Ameliorative effect of naringin in acetaminophen-induced hepatic and renal toxicity in laboratory rats: role of FXR and KIM-1. (2nd July 2016) - Adil, Mohammad; Kandhare, Amit D.; Ghosh, Pinaki; Venkata, Shivakumar; Raygude, Kiran S.; Bodhankar, Subhash L.
Abstract: Context : Acetaminophen (APAP) is an analgesic and antipyretic agent commonly known agent to cause hepatic and renal toxicity at a higher dose. Naringin, a bioflavonoid possesses multiple pharmacological properties such as antioxidant, anti-inflammatory, analgesic and anti-hyperlipidemic activity.Objective : To evaluate the effect of naringin against the APAP-induced hepatic and renal toxicity.Materials and methods : Male Wistar albino rats (180–220 g) were divided into various groups, and toxicity was induced by APAP (700 mg/kg, p.o., 14 days). Naringin (20, 40 and 80 mg/kg, p.o.) or Silymarin (25 mg/kg) was administered to rats 2 h before APAP oral administration. Various biochemical, molecular and histopathological parameter were accessed in hepatic and renal tissue.Results : Naringin pretreatment significantly decreased ( p < 0.05) serum creatinine, blood urea nitrogen, bilirubin, aspartate transaminase, alanine transaminase, lactate dehydrogenase, low-density lipoprotein, very low-density lipoprotein, cholesterol and triglycerides as compared with APAP control rats. Decreased level of serum albumin, uric acid, and high-density lipoprotein were also significantly restored ( p < 0.05) by naringin pretreatment. It also significantly restores ( p < 0.05) the altered level of superoxide dismutase, reduced glutathione, malondialdehyde and nitric oxide in hepatic and renal tissue. Moreover, altered mRNA expression of hepatic farnesoid X receptor and renal injury molecule-1 (KIM-1) were significantly restored ( p < 0.05) by naringin treatment. Naringin treatment also reduced histological alteration induced by APAP in the liver and kidney.Conclusion : Naringin exerts its hepato- and nephroprotective effect via modulation of oxido-nitrosative stress, FXR and KIM-1 mRNA expression.